Ferroptosis and recurrent miscarriage: a critical review of pathophysiology and emerging therapeutic targets - Khodaei, Mohammad Masoud; Noori, Zahra; Zare, Fateme; Meshkin, Ahmad (Frontiers in Cell and Developmental Biology, 2025)
Ferroptosis is characterized as a specialized type of regulated cellular death that relies on iron and lipid peroxidation, which has recently been highlighted as playing a crucial role in the etiology of recurrent miscarriage (RM). Ferroptosis in RM is driven by dysregulated iron metabolism and increased oxidative stress, resulting from impaired antioxidant defense, which leads to lipid peroxidation and consequent cell death in trophoblasts. The cellular changes compromise placental development and impair trophoblast invasion and maternal-fetal tolerance. Therapeutic interventions targeting ferroptosis are promising for the mitigation of its effects and improvement of pregnancy outcomes. Strategies include Glutathione Peroxidase 4 (GPX4) activity enhancement, glutathione replenishment, ferroptosis inhibitors, and iron metabolism modulation. Further, new strategies targeting non-coding RNAs, and epigenetic regulators emphasize ferroptosis as a viable therapeutic target. This review emphasizes the importance of ferroptosis in the pathophysiology of RM and highlights its potential for guiding innovative treatments.